2022
DOI: 10.3389/fevo.2022.999488
|View full text |Cite
|
Sign up to set email alerts
|

Good news! Sampling intensity needed for accurate assessments of dung beetle diversity may be lower in the Neotropics

Abstract: Ecological studies with Scarabaeinae dung beetles have increased exponentially over the past 30 years, using lethal pitfall traps baited with mammal feces or carrion as the preferred sampling method. Different studies have determined the distance between pitfall traps for effective sampling, but the number of traps is often subjective, leading to excessive or poor sampling. This study provides quantitative guidelines for establishing the sample size for optimal completeness of dung beetle diversity by systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…2016). Although it has been argued that Neotropical studies on dung beetles as currently carried out apply an excessive sampling effort (Rivera and Favila 2022), we believe that installing more traps and presenting a broader spatial and temporal distribution in the tepui mountains could present clearer trends regarding beetle elevational distribution.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…2016). Although it has been argued that Neotropical studies on dung beetles as currently carried out apply an excessive sampling effort (Rivera and Favila 2022), we believe that installing more traps and presenting a broader spatial and temporal distribution in the tepui mountains could present clearer trends regarding beetle elevational distribution.…”
Section: Discussionmentioning
confidence: 84%
“…Dry tropical ecosystems (e.g., Caatinga dry forest) are more prone to seasonal fluctuations in beetle activity compared to more humid ecosystems (e.g., Atlantic rainforest; see Liberal et al 2011;Iannuzzi et al 2016). Although it has been argued that Neotropical studies on dung beetles as currently carried out apply an excessive sampling effort (Rivera and Favila 2022), we believe that installing more traps and presenting a broader spatial and temporal distribution in the tepui mountains could present clearer trends regarding beetle elevational distribution.…”
Section: Dependent Variable Statisticsmentioning
confidence: 88%
“…Standardized annual camera trapping protocol to monitor ground‐dwelling mammals and relatively larger vertebrates have been formed (Jansen et al., 2014 ; Meek et al., 2012 ), and some studies have followed these standards (Gorczynski et al., 2021 ). At the same time, several studies have evaluated different factors that influence the capturing efficiencies of pitfall traps for ground‐dwelling invertebrates, such as diameter (Brennan et al., 2005 ), depth (Jiménez‐Carmona et al., 2020 ; Pendola & New, 2007 ), color (Buchholz et al., 2010 ), presence and type of preservative (Luff, 1968 ), sampling duration (Jung et al., 2019 ), and sampling intensity (Rivera & Favila, 2022 ). This study only evaluated the effects of one important factor (i.e., shooting area of ICTs) on the diversity of ground‐dwelling invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Rivera and Favila (2022) demonstrated that ecological studies in the Neotropics often collect more dung beetle individuals than necessary to obtain a representative diversity sample. They suggest that we are currently oversampling the dung beetle community.…”
Section: Type and Number Of Trapsmentioning
confidence: 99%
“…However, if it is not possible to use 100 m, at least a minimum distance of 50 m is recommended. We suggest five or six traps per site (see Rivera and Favila, 2022), therefore considering a transect of 400 m, with five traps spaced at 100 m by type of bait, considered as a replica, and at least three replicas, regarding the distance between sites.…”
Section: Gaps Potential Questions Things To Improve and Recommendationsmentioning
confidence: 99%